PENGGUNAAN APLIKASI COREl DRAW SEBAGAI MEDIA EDITING DIKALANGAN MAHASISWA - M.Aidil Akbar; Sendy Pramana; M.Fauzi; Ainun Harahap; Raja Sakti Arief Daulay (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This socialization activity aimed to introduce the use of CorelDRAW as a graphic editing tool among university students. CorelDRAW was chosen because it is easy to use, flexible, and supports various design needs such as logo creation, posters, flyers, and visual illustrations. The activity was conducted using a descriptive qualitative approach with a participatory method, where students not only received material but also practiced directly. The program involved 12 students and took place at Universitas Pangeran Antasari. The results showed that most participants understood the material well, particularly in recognizing the interface and basic vector drawing techniques. This activity proved to be helpful in improving students' communicative visual design skills to support both academic and organizational purposes.